Effect the Learning by individual lesson for left hand coach in response time and achievement - Abedullah, Alaa (Journal of Physical Education, 2015)
The study aimed to identify the impact of use tow styles in left and right hand's coach in individual lesson on motor response time and achievement (hits rate) for foil fencers. experimental method has been used to carry out research on a subjects consisting of eight foil fencers ages (14 – 15), distributed into two groups. the main conclusions is the individual lesson by left or right hand developed the motor response time for two groups, and developed the hits rate against a left hand fencer for the experimental group. The recommendation indicate to use a left hand in individual lesson in addition to right hand